The Professional Education and Development of Teachers of Mathematics
XII, 280 p.
Keywords: The premise of the 15th ICMI Study is that teachers are key to students' opportunities to learn mathematics. What teachers of mathematics know, care about, and do is a product of their experiences and socialization, together with the impact of their professional education. The Professional Education and Development of Teachers of Mathematics assembles important new international work- development, research, theory and practice - concerning the professional education of teachers of mathematics. As it examines critical areas to reveal what is known and what significant questions and problems warrant collective attention, the volume also contributes to the strengthening of the international community of mathematics educators. Preparing and maintaining a high-quality, professional teaching force that can teach mathematics effectively and prepare youth for a future of social responsibility is a worldwide challenge. As such, systems of teacher education, both initial and continuing, are essential to the success of mathematics educators and their students. More international exchange of knowledge and information about the professional development would certainly benefit both groups, and this volume seeks to address the need. The Professional Education and Development of Teachers of Mathematics offers a cross-cultural conversation about mathematics teacher education in mathematics around the world with attention given to research, theory, practice and policy.